(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The study aimed to test the possibility of camouflaging the southern cowpea beetle to lay its eggs on rhyolite rocks mixed with red cowpea seeds, where it was found that the insect laid its eggs on the seeds in addition to the rocks with which they were mixed. A significant decrease in the rate of the number of eggs laid, as it was found a decrease The rates of the number of eggs laid when the ratio of rocks to seeds was increased reached (66.33, 45.66, 25.33) eggs\20gm while the seeds were mixed with rocks in ratios of (1:1), (2:1), (3:1) respectively, compared to the control that It reached (92.33) eggs, which in turn affected the percentage decrease in the first generation individuals, which amounted to (37.99, 63.31, 84.72)%.